TEACHER'S FEEDBACK ON STUDENTS' DESCRIPTIVE TEXTS: A CASE STUDY CONDUCTED IN A JUNIOR HIGH SCHOOL IN BANDUNG - Pertiwi, Indri Eka (2013)
This study intends to investigate the way of teacher in providing feedback for students' descriptive texts, and examine the responses of the students toward the given feedback. It employed a descriptive case study, involving an English teacher who taught twenty students as the respondents. The data were gathered from classroom observations, questionnaires, and interviews. The obtained data were mainly analyzed based on Hedge (1988), Kaplan & Grabe (1996), Ferris (2002) and Hyland (2003) explaining forms of feedback. The findings showed that the teacher provided four forms of feedback as proposed by Hedge et al (1988); whole class conference, one-on-one conference, commentary, and minimal marking. Most students tended to respond positively toward the feedback provided by the teacher and they considered it helpful for them to write better. In conclusion, feedback from teacher is an essential aspect for students in helping them make better writing. However, for the sake of clarity and understanding, it is also important to pay attention on the forms of feedback given. Penelitian ini ditujukan untuk mengetahui strategi yang digunakan oleh guru dalam memberikan umpan balik (feedback) kepada siswa, khususnya pada teks deskriptif siswa. Penelitian ini menggunakan metode descriptive case study yang melibatkan seorang guru dan dua puluh siswa sebagai respondennya. Data dalam penelitian ini diperoleh dengan observasi, kuesioner, dan wawancara. Data yang telah dieroleh di analsis dengan menggunakan teori Hedge (1988), Kaplan & Grabe (1996), Ferris (2002) and Hyland (2003) yang berkaitan dengan bentuk-bentuk feedback. Hasil penelitian ini menunjukkan bahwa guru tersebut menggunakan empat macam bentuk feedback yang dikemumkakan oleh Hedge, dkk (1988); whole class conference, one-on-one conference, commentary, dan minimal marking. Sebagian besar siswa merespon secara positif feedback yang diberikan oleh guru. Mereka berpendapat bahwa feedback tersebut sangat membantu mereka dalam menulis teks deskriptif dengan lebih baik. Maka dari itu, guru hendaknya dapat mempertimbangkan jenis atau bentuk feedback yang akan diberikan kepada siswa agar siswa dapat memahaminya secara menyeluruh.